The Impact of Universal Coverage Schemes in the Developing World : A Review of the Existing Evidence - Giedion, Ursula; Andrés Alfonso, Eduardo; Díaz, Yadira (World Bank, Washington DC, 2013)
The document is organized as follows. Chapter two provides an introduction to the conceptual framework guiding this study. It is organized in three sections. First, it discusses the concept of universal coverage and the health schemes and programs the concept refers to. Second, it discusses the causal link between universal coverage schemes and health-related outcome indicators. Third, it presents key methodological challenges faced by analysts wishing to evaluate the impact of Universal Health Coverage (UHC) schemes. Chapter three presents the methodology used to search, include, and evaluate the robustness of the existing literature. Chapter four presents the results of our search and inclusion criteria and describes the general characteristics of the literature reviewed. Chapter five provides an analysis of the robustness of the evidence. Chapter six synthesizes the evidence of the literature on the impact of universal coverage schemes in low-income and middle-income countries. Finally, the last chapter summarizes our findings and their policy and research implications.